2020
DOI: 10.3892/ol.2020.12050
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNAs lnc‑ANGPTL1‑3:3 and lnc‑GJA10‑12:1 present as regulators of sentinel lymph node metastasis in breast cancer

Abstract: Long non-coding RNAs (lncRNAs) participate in various biological processed involved in tumorigenesis, metastasis and proliferation. The aim of the present study was to identify candidate long non-coding RNAs (lncRNAs) involved in sentinel lymph node (SLN) metastasis in breast cancer. Specimens of SLNs were collected from patients with SLN metastasis via punch biopsy. Total RNA was extracted and RNA sequencing (RNA-seq) was conducted. Differential expression profiles of mRNAs and lncRNAs were obtained via bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Analysis of the miRNA-mRNA network from multiple studies reveals that miR-34a-5P, with the cooperation of speci c proteins, plays a role in breast cancer and other gynecological cancers as well (48-50). As an example, hsa-miR-34a-5p was discovered in two separate studies published in 2017 and 2020 as a potential marker of metastasis (51,52) and chemo-resistance (53,54) (55). This research reported a negative correlation between miR-501-3p and its target genes, suggesting that this miRNA could be a new candidate for TNBC targeted therapies.…”
Section: Discussionmentioning
confidence: 91%
“…Analysis of the miRNA-mRNA network from multiple studies reveals that miR-34a-5P, with the cooperation of speci c proteins, plays a role in breast cancer and other gynecological cancers as well (48-50). As an example, hsa-miR-34a-5p was discovered in two separate studies published in 2017 and 2020 as a potential marker of metastasis (51,52) and chemo-resistance (53,54) (55). This research reported a negative correlation between miR-501-3p and its target genes, suggesting that this miRNA could be a new candidate for TNBC targeted therapies.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, hepatocellular carcinoma (HCC) [ 29 ], pancreatic cancer [ 30 ], and other cancers have become significant prognostic markers. The gap junction α (GJA) family has been demonstrated to be involved in the cellular proliferation and metastasis of gastric cancer and breast cancer [ 31 , 32 ]. In the current study, we found that CYSLTR2 [ 33 , 34 ], CYP4Z1 [ 35 ], LINC00324 [ 36 ], and PTCSC3 [ 37 ] have shown a close relationship with the initiation and development of tumors and also with the prognosis of the COAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs regulate cell progression through targeting miRNAs or mRNA (Gutschner and Diederichs, 2012;Paraskevopoulou and Hatzigeorgiou, 2016). More and more evidence shows that lncRNAs can be used as important molecular markers involved in gene regulation and cell progression (Sun et al, 2020). Mini-chromosome maintenance complex component 2 (MCM2) gene is a major gene affecting the stability of micro mitotic chromosomes Ⅲ, and MCM2 protein is a family member that initiates DNA replication and maintains progression in the cell cycle (Gottesman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%